Negotiating Engagement and Digital Distraction: English Teachers’ Pedagogical Adaptation for Generation Z in Secondary Classrooms - Aulia Rachmad Pidie Saputra; Suhaimi; Reko Hary Putra (CV. DYOQU PUBLISHING MANAGEMENT, 2026)
Background: The emergence of Generation Z has significantly transformed English language classrooms by introducing learning preferences shaped by digital immersion, rapid information access, and interactive communication environments. These characteristics challenge conventional teacher centered pedagogy and create a complex tension between learning engagement and digital distraction in secondary education settings. Aims: This study examines how English teachers adapt their pedagogical practices to engage Generation Z learners while simultaneously managing the challenges of digital distraction within secondary school classrooms. Methods: A qualitative descriptive design was employed. Data were collected through semi structured interviews, classroom observations, and instructional document analysis involving English teachers who regularly teach digitally oriented learners. The collected data were analyzed using thematic analysis to identify recurring patterns of instructional challenges and adaptive pedagogical strategies. Results: The findings indicate that multimedia materials, collaborative learning tasks, and technology integrated activities increase student participation, motivation, and classroom interaction. Nevertheless, teachers continue to encounter persistent difficulties in maintaining sustained student attention, controlling off task digital behavior, and ensuring that technological tools remain aligned with pedagogical objectives. Conclusion: The study demonstrates that effective instruction for Generation Z learners requires adaptive pedagogy that integrates digital technology with learner centered instructional design, structured interaction, and guided participation. Teachers must strategically transform digital engagement into productive learning opportunities rather than uncontrolled technological use. Strengthening teachers’ digital pedagogical competence and providing institutional support are therefore essential to ensure that technology enriched classrooms promote sustained engagement, meaningful communication, and deeper language learning outcomes.